Tomorrow's silk road : assessing an EU-China free trade agreement - Pelkmans, Jacques (CEPS ; Rowman and Littlefield International, 2018)
The first comprehensive and in-depth economic and regulatory analysis of a possible Free Trade Area (FTA) between China and the EU.